(untitled) (Bangladesh Journal of Nutrition, 2018)
A cross-sectional study was conducted to assess the nutritional status of randomly selected 120 consumers of street foods of a private University at Dhaka. The data on socioeconomic information, nutritional status, street food preference, personal hygiene and occurrence of diseases was collected using a structured questionnaire. Nutritional status was determined by BMI. Statistical analysis was done by using the SPSS and Microsoft excel. As revealed in the study, 76.7% of the respondents were male, 58.3% belonged to middle income group and 76.7% respondent’s educational expenses were borne by their parents. Street foods were preferred by 24.2% consumers because of their good taste and quick service. The most preferred street foods were Shingara, Samucha and Puri. Street foods were stated as unhealthy by 56.7% consumers. Among them 16.7% had under nutrition, 23.3% had over nutrition and 60%had normal nutrition status. There is a significant association between nutritional status and hygienic practices (p value= 0.046). But 38.3% with normal nutritional status suffered from various diseases. There is no significant relationship between the street food consumption and nutritional status. More frequent street food consumption might have unhealthy effect on nutritional status. Therefore, further studies are required to evaluate the effect of frequent street food consumption on nutritional status. Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 55-63